Damage of additively manufactured polymer materials: experimental and probabilistic analysis (Fracture and Structural Integrity, 2025)
This paper presents a study on the tensile, fracture, damage, and reliability properties of 3D printed polylactic acid (PLA), based on a series of experiments. The study focuses on polylactic acid (PLA) samples produced using fused filament manufacturing (FFF) technology, specifically examining unidirectional print orientations of 0°, 45°, and 90°. Tensile testing demonstrated significant anisotropy in mechanical behavior, The specimens oriented at 0° exhibited the highest tensile strength, while those at 90° showed the lowest. An increase in artificial crack length (a) resulted in a progressive decrease in the mechanical properties. Weibull analysis confirmed the presence of significant anisotropic behavior in 3D-printed PLA specimens, with ultimate stress (σu0) values ranging from 39.82 MPa for the 90° orientation to 44.69 MPa for the 0° orientation, and elastic stress (σe0) values from 35.49 MPa (90°) to 39.11 MPa (0°), indicating greater strength for the 0° oriented specimens. Damage evolution analysis showed accelerated damage, with the 90° orientation demonstrating the fastest rate of damage compared to the 0° and 45° orientations. This indicates that the 90° orientation is more vulnerable to crack propagation and has diminished structural integrity under stress.
Keywords: Damage evolution; Reliability; additive manufacturing; 3D crack propagation; fracture mechanics; 3D-printing